Travel Agency Companies Under Environmental Uncertainty: Multiple Strategic Orientation and Performance - Muhadjir Anwar; Ayundha Evanthi; Eko Purwanto (Jurnal Manajemen Teknologi, 2025)
Abstract. The tourism sector, the economy, and the industries that support it have all been severely damaged by the worldwide pandemic. Several of the tourism industry's market segments, such as lodging, dining, and travel agencies, are at saturation. To maintain a sustainable competitive advantage and achieve the intended results, companies need to have a well-defined plan of action to navigate the constantly shifting business landscape. This study will examine the mediating role of organizational strategic orientation in the performance of travel agency companies in the face of environmental uncertainty. The data is collected via a questionnaire and then PLS-SEM analysis is performed. The results show that the choice of an organization's strategic orientation, which includes market and entrepreneurial orientations that can impact learning orientation and organizational performance of travel agency companies, is influenced by technology uncertainty. As a component of a vibrant and alluring travel industry, travel agency businesses must be flexible and inventive in the face of ongoing technological advancements. This can be achieved through organizational strategy orientation, which emphasizes market and entrepreneurial orientations to boost the performance of travel agency businesses. Keywords:  Organizational Strategy Orientation, Environmental Uncertainty, Organizational Performance